Reducing Activity of Interleukin-8 (IL-8) Extract of Sea Cucumber (Holothuroidea sp.) in Experimental Animals Induced by Carrageenan - Aurum, Mursalina Nanda; Suhendi, Andi; Da'i, Muhammad; Fauzi, Ahmad (Universitas Muhammadiyah Surakarta, 2024)
Interleukin-8 is a pro-inflammatory cytokine that plays a role in the inflammatory response. Sea cucumbers (Holothuria sp.) are used as alternative medicines that have anti-inflammatory activity. The study aims to determination of Sea cucumber (Holothuria sp.) as anti inflammation activty based on capability of reducing interleukin-8 (IL-8) on Rats induced by Carrageenan. Experimental research used was a post-test-only control group design. A total of 25 rats were divided into 5 groups, namely negative control, positive control (Na. Diclofenac), and treatment groups given Sea cucumber extract (doses of 45, 90, and 180 mg/ g BW). Carrageenan-induced mouse paw edema model was used for induction of inflammation. IL-8 of Paw tissue were measured by an ELISA reader at 450 nm wavelength. The result showed that treatrment groups has anti-inflammation activity based on IL-8 levels compared to negative and positive controls. The lowest levels of IL-8 showed at a dose of 90 mg/g BW. Based on One-way ANOVA, there were no significant differences of between groups. Sea cucumber has anti-inflammation activity by reducing IL-8 at all dose tested